Implementasi Tema Rempah Dan Cerita Rakyat Nusantara Dalam Komik Fiksi - Ferry Setiawan, Marshall (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2023)
In addition to biodiversity, Indonesia also has culturaldiversity with the uniqueness of each region that producesproducts in form of folklore. This encourage the artist tomake a fictional comic with the theme of spices andIndonesian folklore which is expected to function as analternative media that can help introducing spices andIndonesian folklore. The concept of this design is a fictionalcomic with theme of clove spice and Maluku folklore“Buaya Tembaga” as well as pepper spice and Aceh folklore “Kisah Tujuh Anak Lelaki” which will be made intoa physical comic book with paneled illustrationvisualizations using the artist’s art style. Making of thisartwork is using research-led practice method, whichpractice is based on field research and references availablein internet and books about folklore and spices, and thenapplied in the process of making the comic as an artcreation thesis work. Overall, the creation of this work is in the form of fictionalcomics made with digital drawing techniques. The comicsare designed through various exploration and data collection independently as well as using surveys. The worksfeatured in this creation are the comic titled “Liam dan Buaya Tembaga” and “Petualangan di Hutan Raksasa”.The creation of this works is hoping to produce a new fictionstory that can be a media to introduce Indonesian folkloreand benefit of spices to the public.